Measuring the Contribution of Faith-Based Schools to Human Capital Wealth : Estimates for the Catholic Church - Wodon, Quentin (Taylor and Francis, 2019)
This paper provides estimates of the contribution of faith-based schools to human capital wealth using recent World Bank data. Wealth is the assets base that enables nations to generate future income. Estimates suggest that human capital wealth accounts for two thirds of global wealth, a much larger proportion than natural capital and produced capital. This paper’s analysis relies on an assessment of the share of human capital wealth attributed to educational attainment, and the share of contribution of Catholic schools to educational attainment. The analysis suggests that Catholic schools contribute at least US$ 12 trillion to the changing wealth of nations.